2013 IEEE International Conference on Robotics and Automation 2013
DOI: 10.1109/icra.2013.6631418
|View full text |Cite
|
Sign up to set email alerts
|

3D flexible needle steering in soft-tissue phantoms using Fiber Bragg Grating sensors

Abstract: Needle insertion procedures are commonly used for surgical interventions. In this paper, we develop a threedimensional (3D) closed-loop control algorithm to robotically steer flexible needles with an asymmetric tip towards a target in a soft-tissue phantom. Twelve Fiber Bragg Grating (FBG) sensors are embedded on the needle shaft. FBG sensors measure the strain applied on the needle during insertion. A method is developed to reconstruct the needle shape using the strain data obtained from the FBG sensors. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 32 publications
1
71
1
1
Order By: Relevance
“…In the current study, we demonstrate using an array of FBG [19]. However, the tip deflections in that study were small (i.e., ≤ 5 mm) compared to our study.…”
Section: Introductioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In the current study, we demonstrate using an array of FBG [19]. However, the tip deflections in that study were small (i.e., ≤ 5 mm) compared to our study.…”
Section: Introductioncontrasting
confidence: 68%
“…This curvature is then used to reconstruct the 3D instrument shape. Previous studies have used FBG sensors to reconstruct the shape of a colonoscope and flexible surgical needles [15]- [19]. These studies have shown that instrument shape can be reconstructed with high accuracy using FBG sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, innovative needle designs focus on the steerability of needles, either manually or robotically inserted, aiming to steer towards a hard-to-reach target and possibly to avoid anatomical obstacles (e.g. [7][8][9]). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used FBG sensors to determine deflected needle shapes during insertion into soft tissues [20], [21]. Accurate reconstruction of needle shape has been demonstrated using this method.…”
Section: Introductionmentioning
confidence: 99%